Analisis Kinerja Keuangan dari Aspek Likuiditas dan Profitabilitas pada PT Indofood Sukses Makmur Tbk Indonesia Tahun 2021–2023 - Tomi Irianto; Amran Manurung (Lembaga Yasin AlSys, 2026)
The importance of financial performance analysis has increased along with increasingly competitive business competition, particularly in companies in the food and beverage sector. In this context, financial performance is the main indicator for assessing a company’s ability to manage resources and maintain business sustainability. This study aims to analyze the financial performance of PT Indofood Sukses Makmur Tbk based on liquidity ratios and profitability ratios in the 2021–2023 period. This study employed a descriptive method with a quantitative approach. The data used were secondary data from the company’s annual financial statements obtained through the official website of Bursa Efek Indonesia. Data analysis was conducted using financial ratios, including the Current Ratio and Quick Ratio as indicators of liquidity, as well as Return on Assets (ROA) and Return on Equity (ROE) as indicators of profitability. The results showed that the financial performance of PT Indofood Sukses Makmur Tbk from the liquidity aspect was still below industry standards, so the company’s ability to meet short-term obligations was considered not yet optimal. From the profitability aspect, ROA showed a relatively low value compared with industry standards, whereas ROE showed fairly good performance because the company was able to generate profit from its existing capital. Thus, it can be concluded that the company’s financial performance still needs to be improved, especially in asset management so that its ability to generate profit becomes more optimal. These findings provide a practical contribution to the evaluation of the financial performance of companies in the food and beverage sector and serve as a basis for consideration in managerial decision-making related to liquidity and profitability.